The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0078945
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Effects of Elevated CO2 on Shell Composition and Mechanical Properties of Hydroides elegans: Insights from a Multiple Stressor Experiment

Abstract: The majority of marine benthic invertebrates protect themselves from predators by producing calcareous tubes or shells that have remarkable mechanical strength. An elevation of CO2 or a decrease in pH in the environment can reduce intracellular pH at the site of calcification and thus interfere with animal’s ability to accrete CaCO3. In nature, decreased pH in combination with stressors associated with climate change may result in the animal producing severely damaged and mechanically weak tubes. This study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 81 publications
(107 reference statements)
3
21
0
Order By: Relevance
“…An observation that amorphous matter content in Hydroides elegans shows negative correlation with temperature (Chan et al, 2013), generally agrees with our data on Spirorbini (IOP structure of warm-water Groups A and C has low cement content, while relatively coldwater Group B always demonstrates high cement content).…”
Section: Interpretation Of Subdivision Into A-c Groupssupporting
confidence: 92%
“…An observation that amorphous matter content in Hydroides elegans shows negative correlation with temperature (Chan et al, 2013), generally agrees with our data on Spirorbini (IOP structure of warm-water Groups A and C has low cement content, while relatively coldwater Group B always demonstrates high cement content).…”
Section: Interpretation Of Subdivision Into A-c Groupssupporting
confidence: 92%
“…However, the tubes that are formed at lower CaCO 3 saturation may be more fragile. This is in line with results from cultured juvenile worm tubes of the tropical serpulid species Hydroides elegans, which showed reductions in shell hardness and wall thickness at lowered pH and CaCO 3 saturation states (Chan et al, 2012(Chan et al, , 2013Li et al, 2014).…”
Section: Growth Ratesupporting
confidence: 89%
“…Several recent ocean acidification experiments have included serpulid worms of a variety of species. Most studies focused on the tropical species Hydroides elegans (Lane et al, 2013;Chan et al, 2012Chan et al, , 2013Mukherjee et al, 2013;Li et al, 2014). The results indicated reduced growth, increased porosity and reduced mechanical strength of the worm tubes, as well as increased mortality of larvae at lowered pH (<7.9).…”
mentioning
confidence: 99%
“…For example, Chan et al (2013) found that elevated temperature offset the negative effects of reduced pH and salinity on the accretion and strength of calcareous tubes of tropical tubeworms [67]. Similarly, moderate warming was found to slightly ameliorate the negative effects of OA on the shell growth of larval oysters (although more extreme warming exacerbated the effects of OA) [68].…”
Section: Discussionmentioning
confidence: 99%